2014
DOI: 10.1074/jbc.m114.614529
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of an Unusual Hopanoid-containing Lipid A Among Lipopolysaccharides from Bradyrhizobium Species

Abstract: Background: Hopanoids are present in bradyrhizobial lipid A preparations. Results: Signals from hopanoid carboxyl shows strong correlation with the proton geminal to the hydroxy group of ester-linked long chain fatty acid. Conclusion: Hopanoids are covalently linked to the lipid A of Bradyrhizobium. Significance: The presence of such an unusual lipid A substituent may have a strong influence on the membrane properties of Bradyrhizobium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 49 publications
1
39
0
1
Order By: Relevance
“…Hopanoids have been identified in the OM of diverse bacteria (29,(43)(44)(45)(46), and two recent studies have reported a covalently linked hopanoid-lipid A compound in rhizobial plantassociated bacteria (47,48). These observations suggest that hopanoid-lipid A ordering may be widespread among hopanoid-producing bacteria.…”
Section: Discussionmentioning
confidence: 74%
“…Hopanoids have been identified in the OM of diverse bacteria (29,(43)(44)(45)(46), and two recent studies have reported a covalently linked hopanoid-lipid A compound in rhizobial plantassociated bacteria (47,48). These observations suggest that hopanoid-lipid A ordering may be widespread among hopanoid-producing bacteria.…”
Section: Discussionmentioning
confidence: 74%
“…However, it is also possible that the relevance of hopanoids in Bradyrhizobium spp. symbioses can be attributed to the presence of an unusual lipid A structure: hopanoid-lipid A (HoLA), in which lipid A is covalently attached to an extended hopanoid polyol 113,115,116 (FIG. 4).…”
Section: Biological Functions Of Hopanoidsmentioning
confidence: 99%
“…The latter were both ester‐linked to the primary acyl chains at positions 3′ and 2′, respectively, of the non‐reducing Glc p N3N unit. As previously mentioned, it is worth underlining that R. palustris is genetically related to the Bradyrhizobium genus, and this relationship was also clearly evident in comparisons with the recently elucidated lipid A from Bradyrhizobium strains such as BTAi1 . Indeed, besides the above described similarities concerning the sugar backbone, the presence in R. palustris strain BisA53 lipid A of an amide‐linked acyloxyacyl residue on the non‐reducing GlcN3N, on which the VLCFA 26:0(25:OAc) is appended as a secondary acyl moiety, is a structural lipid A feature in common with Bradyrhizobium strains.…”
Section: Discussionmentioning
confidence: 60%
“…Thus, R. palustris strain BisA53 has a novel lipid A structure (Figure ), in which the sugar backbone is built up of a β‐(1→6)‐linked Glc p N3N disaccharide and an α‐Gal p A residue connected to the reducing end of the Glc p N3N through an α‐(1→1) glycosidic linkage, in addition to an α‐Man p unit linked at position O4 of the non‐reducing β‐Glc p N3N residue. To date, another bacterium belonging to the Rhopseudomonas genus, namely R. viridis , as well as Rhizobiaceae (i.e., Brady ‐, Azo ‐, and Mesorhizobium genera) have been reported to be characterized by the occurrence of a Glc p N3N disaccharide backbone in place of the most common Glc p N disaccharide. Interestingly, the biosynthetic pathways of both types of lipid A sugar skeleton (namely the Glc p N and the Glc p N3N disaccharide) were proven to be similar and two enzymes, GnnA and GnnB, have been identified as being responsible for the synthesis of UDP‐ d ‐Glc p N3N from UDP‐ d ‐Glc p NAc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation